2021
DOI: 10.5546/aap.2021.eng.192
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin G use and pharmacovigilance in a tertiary care children’s hospital

Abstract: Introduction. Intravenous immunoglobulin G (IVIG) is a blood product from polyvalent and polyclonal immunoglobulin G. It covers a broad range of indications as immunomodulator or replacement therapy. In addition, although it is considered a safe therapy, the incidence of adverse reactions reported in the bibliography ranges from 1 % to 81 %. The objective of this study was to assess IVIG use and describe related adverse events in a tertiary care children's hospital. Population and methods. This was a pharmacoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Aside from analyzing data from the database, the researchers also conducted prospective pharmacoepidemiology studies using patients from children’s hospitals. Yori et al 42 analyzed 111 pediatric patients receiving intravenous immunoglobulin G and found that the incidence of adverse reactions was relatively low and could be treated effectively. A Canadian Pediatric Surveillance Program (CPSP) Study found that if a pediatric patient’s parents have acanthosis nigricans or type 2 diabetes (T2D), blood glucose should be closely monitored when using diabetogenic medication.…”
Section: Child Patientmentioning
confidence: 99%
“…Aside from analyzing data from the database, the researchers also conducted prospective pharmacoepidemiology studies using patients from children’s hospitals. Yori et al 42 analyzed 111 pediatric patients receiving intravenous immunoglobulin G and found that the incidence of adverse reactions was relatively low and could be treated effectively. A Canadian Pediatric Surveillance Program (CPSP) Study found that if a pediatric patient’s parents have acanthosis nigricans or type 2 diabetes (T2D), blood glucose should be closely monitored when using diabetogenic medication.…”
Section: Child Patientmentioning
confidence: 99%